Is the family really an outdated institution in Italy as well as in Europe? Findings from the European Values Study - Bosoni, Maria Letizia; Mazzucchelli, Sara (Socialinė teorija, empirija, politika ir praktika, 2017)
The concept of institution, one of the main issues in the social sciences, has been developed in a number of anthropological, economical, juridical, political, and sociological institutional theories. There is no overarching theory, however, to explain what institutions are for, how they are formed and why they change. This contribution takes into account, in particular, the institution of the family as a fundamental institution of society, not only because it ensures reproduction over time but because it shapes the personal and social identity through socialization of new generations, and will verify whether the family is still considered valid as an institution. In particular, the research questions to be addressed are: is the (marriage-based) family still considered a valid institution by Italians and Europeans? Is it possible to identify specific elements linked to a strong idea of the family? Which elements? Using data from the European Values Study (EVS) 2008–2009, an index was devised to measure the (high, medium, low) importance attributed to the family as a social institution, and its structural and cultural characteristics in both Italy and Europe (with a total of 28 countries considered), as well as with clusters correlated to it.